Synthesis and characterization of gadolinium and gold-doped layered double hydroxide and graphene oxide nanocomposites for therapeutic agent delivery - Usman, Muhammad Sani (2018)
Multimodal delivery system (MDS) or theranostic delivery system (TDS) is still at its infancy. In this work, the concept of MDS was employed, where magnesium/zinc aluminium-layered double hydroxides (Zn/Mg-Al LDH) and graphene oxide (GO) were used as nanocarriers (host) to intercalate and adsorb therapeutic agents (chlorogenic acid, prochatetuic acid and gallic acid), and contrast agents; gadolinium (Gd) as well as gold nanoparticles (AuNPs) as guest molecules. The Gd contrast agent was used as the main contrast agent for magnetic resonance imaging (MRI) and the AuNPs served as supporting contrast agent. The therapeutic and contrast agents were used to develop various the LDH and GO-based nanocomposites. The agents were developed based on ion exchange interaction in the LDH and non-covalent π-π stacking bonding and OH/COOH hydrogen bonding in the GO. The synthesis routes adopted were the Hummer’s modified method for GO and co-precipitation for LDH. The mechanism and physico-chemical properties of the nanocomposite formation were studied via characterization processes, such as transmission electron microscopy (TEM) and field emission scanning electron microscopy (FESEM), which were used for shape, size and morphological studies. Fourier transformed-infrared spectroscopy (FTIR) and Raman spectroscopy were used for chemical interaction studies. Inductive coupled plasma emission spectroscopy (ICP‒ES), carbon, hydrogen, nitrogen and sulphur analysis (CHNS) and energy-dispersive X-ray (EDS) were used to study the composition as well as purity of the samples. The crystallinity and phase change was studied with X-ray diffraction (XRD) and the ultra violet – visible spectroscopy (UV-Vis) was used for drug release study. The anticancer efficacies of the nanocomposites and the pure phases were evaluated using human liver cancer cell lines (HepG2) and mouse fibroblast cell lines (3T3) were used in cytotoxicity studies. The inherent signal optimization was done on a 3 Tesla MRI machine, to determine the diagnostic properties of the nanocomposites. Subsequent amounts of the loaded therapeutic agents were estimated between 15-60%, depending on the nanocarrier and the therapeutic agent. All the pharmacokinetic releases of the therapeutic agents were best fitted to the pseudo-second order kinetic model. The XRD analysis results confirmed the drug intercalation in the LDH galleries and adsorption on the GO surface. Similarly, the FTIR and Raman spectroscopy confirmed the bonding that occurred between the host and guest molecules. CHNS, ICP‒ES and EDX equally showed the presence of all the intended compounds and elements in the nanocomposites. The AuNPs grown on the LDH and GO nanocomposites as observed from TEM and FESEM micrographs were poly-dispersed with various shapes and sizes (2-120 nm). The nanocomposites were observed to inhibit growth of HepG2 cells and showed less toxic in the 3T3 cell lines. Preliminary MR imaging contrast properties test conducted showed enhanced T1 and T2 signals in the samples containing the nanocomposites. Based on the highlighted results, TDS could serve as potential replacement for the incumbent toxic anticancer agents, which could be used simultaneously in diagnosis.